History 4° celsius : search for a method in the age of the Anthropocene - Baucom, Ian, 1967- (Theory in forms., 2020)
"HISTORY 4° CELSIUS links the Anthropocene with the Atlantic slave trade along Ghana's Gold Coast. The slave trade gave birth to a new epoch, an age of modernity that changed both the political and the natural world. The book describes the relationship between Ghana's Gold Coast's slave factories, built to enclose human beings, the New World plantations, and post-emancipation ghettos and post-colonial shanty-towns. The book's title is taken in part from Sartre's "The Search for Method," and in part from a climate change report, "4°--Turn Down the Heat: Why a 4°C Warmer World Must be Avoided," which notes the danger of a "4° C change above average pre-industrial era temperature levels." Ian Baucom begins with the factory system that warehoused human cargo before slave ships set sail. Focusing on one of the 48 slave forts, Fort William in Anomabo, he argues that Ghana is central to understanding the modern world because the finance capital that spanned the globe and could not have come into being without the slave trade. In his previous work, Specters of the Atlantic, Baucom used the story of the British slave ship Zong, in which 133 slaves were thrown overboard in September 1781 so that the ship's owner could file an insurance claim, to illustrate how commoditizing human life formed the basis of an economic cycle that continues today. Going further in this new work, Baucom argues that the conditions that made the Zong episode possible are continuous with those that impact nature today. As the slave trade and the devaluing of life was driven by financial gain, so greenhouse gas emissions that warm the planet have their roots in profit. Merging seemingly unrelated threads, Baucom draws from "Black Atlantic" imagery of the art world, Marxist thought, Sartrean concepts, and the science of climate change to dissect how evolving political and cultural history and the world's natural history converge to shape modern man as a globally destructive, catastrophic force. He concludes that the modern world can no longer be viewed through the lens of Kant's allegory of a world divided between "nature" and its "political" opposite. Likewise, freedom cannot be understood as simply physical freedom from slavery but must include the challenge of freedom from exposure to the extreme conditions that climate change produces. While Baucom begins with the historical context of Ghana's slave coast, he ends with his eye on the future, insisting that the day of tyrannical state is over and that the way forward is a radical rethinking of freedom-- not "freedom from" but "freedom toward." He challenges the collective disciplines to combine in a "labor of thought," using their methodologies "for making something of what we have been made." Historical, human, and climate forces are not autonomous but interrelated, reinforcing one another"--